REASONING DISCREPANCIES BETWEEN FATHERS AND ADOLESCENTSB ABOUT USE OF DRUGS - Palacios Navarro, Santiago; Palacios Navarro, Mª Blanca (Anales de Psicología / Annals of Psychology, 2002)
The aim of this article is to analyse conflicts between parents and adolescents by means of the study of discrepancies and similarities in the judgement and reasoning on the use of different drugs. While in the first part we try to explain the social domain theory, that is the methodology underlying our investigation, in the second part of the article the results are showed. The results confirm several previous studies (Smetana, 2000; Goñi, 2000b) pointing out the low frecuency of conflicts between parents and adolescent due to discrepancies in matters regarding the use of drugs. However, conflict is possible and actual because results show significant differences between parents and adolescent when they make judgements and reasoning on drugs and their use.